2005
DOI: 10.1016/s0002-9440(10)62351-6
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Epithelial-Mesenchymal Transition in Alveolar Epithelial Cells by Transforming Growth Factor-β1

Abstract: The hallmark of idiopathic pulmonary fibrosis (IPF) is the myofibroblast, the cellular origin of which in the lung is unknown. We hypothesized that alveolar epithelial cells (AECs) may serve as a source of myofibroblasts through epithelial-mesenchymal transition (EMT). Effects of chronic exposure to transforming growth factor (TGF)-beta1 on the phenotype of isolated rat AECs in primary culture and a rat type II cell line (RLE-6TN) were evaluated. Additionally, tissue samples from patients with IPF were evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

43
740
4
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 878 publications
(800 citation statements)
references
References 68 publications
43
740
4
3
Order By: Relevance
“…The excessive activation of fibroblasts and the collagen deposition in the extracellular matrix coincide with the occurrence of EMT 39. It has been demonstrated that alveolar epithelial cells, especially type II alveolar epithelial cells, acquire the phenotype of fibroblasts through EMT to promote the development of pulmonary fibrosis 40, 41. A549 cells retain the features of type II alveolar epithelial cells although they are a type of cancer cells 42, and this cell line is widely used to study the mechanism of pulmonary fibrosis 43, 44, 45.…”
Section: Discussionmentioning
confidence: 99%
“…The excessive activation of fibroblasts and the collagen deposition in the extracellular matrix coincide with the occurrence of EMT 39. It has been demonstrated that alveolar epithelial cells, especially type II alveolar epithelial cells, acquire the phenotype of fibroblasts through EMT to promote the development of pulmonary fibrosis 40, 41. A549 cells retain the features of type II alveolar epithelial cells although they are a type of cancer cells 42, and this cell line is widely used to study the mechanism of pulmonary fibrosis 43, 44, 45.…”
Section: Discussionmentioning
confidence: 99%
“…Epithelial cells acquire phenotypic mesenchymal (fibroblast) markers when exposed to TGF-␤. 43 With respect to the importance of MMPs in EMT, Illman et al 44 reported that epilysin (MMP-28) can induce EMT, leading to cell invasion in lung adenocarcinoma cells through a TGF-␤-dependent mechanism. Additionally, there is strong evidence that MMP-3 can induce EMT in mouse mammary epithelial cells though alteration in Rac1b, a splice variant of Rac1, leading to increases in reactive oxygen species resulting in EMT.…”
Section: Discussionmentioning
confidence: 99%
“…Type II alveolar epithelial cells have been shown to acquire a fibroblast‐like phenotype through EMT to promote the progression of pulmonary fibrosis 3, 4. These cells promote collagen deposition in the extracellular matrix.…”
Section: Introductionmentioning
confidence: 99%